Slip and fall : two years later, has anything changed? - Rossi, Anthony (Continuing legal education (Law Society of South Australia), 2004)
During the last 2 years, slips, trips and the like have continued to occur in circumstances where plaintiffs have claimed to be entitled to damages at common law. This paper addresses the final report of the review of the Law of Negligence, legislative changes particularly in South Australia and some recent decisions locally and interstate.